Longitudinal changes in intracardiac repolarization lability in patients with implantable cardioverter-defibrillator - Guduru, Abhilash; Lansdown, Jason; Chernichenko, Daniil; Berger, Ronald; Tereshchenko, Larisa G. (Frontiers in Physiology, 2013)
Background─While it is known that elevated baseline intracardiac repolarization lability is associated with the risk of fast ventricular tachycardia (FVT) /ventricular fibrillation (VF), the effect of its longitudinal changes on the risk of FVT/VF is unknown. Methods and Results─Near-field (NF) right ventricular (RV) intracardiac electrograms (EGMs) were recorded every 3-6 months at rest in 248 patients with structural heart disease (mean age 61.2±13.3; 185[75%] male; 162[65.3%] ischemic cardiomyopathy) and implanted cardioverter-defibrillator (ICD) or cardiac resynchronization therapy defibrillator (CRT-D) [201 (81%) primary prevention]. Intracardiac beat-to-beat QT variability index (QTVINF) was measured on NF RV EGM. During the first study phase (median 18 months), participants made on average 2.4 visits. Then remote follow-up was continued for an additional median period of 3 years. Average QTVINF did not change during the first year after ICD implantation (-0.342±0.603 at baseline vs. -0.262±0.552 at 6 months vs. -0.334±0.603 at 12 months); however, it decreased thereafter (-0.510±0.603 at 18 months; P=0.042). Adjusted population-averaged GEE model showed that the odds of developing FVT/VF increased by 75% for each 1 unit increase in QTVINF. (OR 1.75 [95%CI 1.05-2.92]; P=0.031). However, individual patient–specific QTVINF trends (increasing, decreasing, flat) varied from patient to patient. For a given patient, the odds of developing FVT/VF were not associated with increasing or decreasing QTVINF over time (OR 1.27; [95%CI 0.05–30.10]; P = 0.881). Conclusion─While on average the odds of FVT/VF increased with an increase in QTVINF, patient-specific longitudinal trends in QTVINF did not affect the odds of FVT/VF.